Mortality among Coast Guard Shipyard workers: A retrospective cohort study of specific exposures. Issue 1 (2nd January 2018) - Rusiecki, Jennifer; Stewart, Patricia; Lee, Dara; Alexander, Melannie; Krstev, Srmena; Silverman, Debra; Blair, Aaron
ABSTRACT: In a previous analysis of a cohort of shipyard workers, we found excess mortality from all causes, lung cancer, and mesothelioma for longer work durations and in specific occupations. Here, we expand the previous analyses by evaluating mortality associated with 5 chemical exposures: asbestos, solvents, lead, oils/greases, and wood dust. Data were gathered retrospectively for 4, 702 workers employed at the Coast Guard Shipyard, Baltimore, MD (1950–1964). The cohort was traced through 2001 for vital status. Associations between mortality and these 5 exposures were calculated via standardized mortality ratios (SMRs). We found all 5 substances to be independently associated with mortality from mesothelioma, cancer of the respiratory system, and lung cancer. Findings from efforts to evaluate solvents, lead, oils/greases, and wood dust in isolation of asbestos suggested that the excesses from these other exposures may be due to residual confounding from asbestos exposure.